Kadar Ischemia Modified Albumin pada pasien Angina Pektoris Stabil yang menjalani Percutaneous Coronary Intervention - Hariadi Hariawan; Otte J Rachman; Yoga Yuniadi (Jurnal Kardiologi Indonesia, 2007)
Background. Ischemia Modified Albumin (IMA) is a biomarker of myocardial ischemia. Blood levels of IMA rise in patients who develop ischemia during percutaneous coronary intervention (PCI). This study evaluated the relation between IMA levels and variables of procedure during coronary angioplasty such as number of balloon inflations, inflation pressure and duration of inflations in patients with stable angina pectoris who underwent PCI. Methods and results. Twenty three consecutive patients (21 men and 2 women), range of age 41 to 80 years old with stable angina pectoris underwent elective PCI between March to April 2006. Blood samples were drawn from femoral or radial artery sheath 10 minutes before PCI and 10 minutes after the last balloon inflation for IMA levels measurement. IMA levels increased positive from 95.26+8.44U/mL before PCI to a level 135.07+18.80U/mL after PCI (p<0.0001). All of the patients used stents except in 2 cases. There are significant correlation between elevation of IMA levels with number of balloon inflation (r=0.59;p=0.003), total pressure inflation (r=0.48;p=0.02) and total duration of balloon inflation (r=0.48;p=0.02).Conclusion. Ischemia Modified Albumin (IMA) levels significantly elevated after percutaneous coronary angioplasty (PCI). There were positive correlation between numbers of inflations, total pressure and total duration of balloon inflations.